2018
DOI: 10.1002/cjp2.105
|View full text |Cite
|
Sign up to set email alerts
|

Replacement and desmoplastic histopathological growth patterns: A pilot study of prediction of outcome in patients with uveal melanoma liver metastases

Abstract: Up to 50% of uveal melanomas (UM) metastasise to the liver within 10 years of diagnosis, and these almost always prove rapidly fatal. As histopathological growth patterns (HGPs) of liver metastases of the replacement and desmoplastic type, particularly from colon and breast carcinoma, may import valuable biological and prognostic information, we have studied HGP in a series of 41 UM liver metastases originating from 41 patients from the period 2006–2017. Twenty patients underwent enucleation while 21 had radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
47
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 46 publications
9
47
1
Order By: Relevance
“…Any tumour infiltrating lymphocytes (TILs) present in mUM were CD8+ T-cells with low expression of cytotoxic markers, such as Granzyme B, and they were typically “excluded” from the tumour core [ 25 ]. These results, which were supported by others and suggest CD8+ T-cell exhaustion [ 27 , 28 ], were corroborated by our earlier study using NanoString analyses of six hepatic mUM by Figueiredo et al 2020 [ 26 ]. We showed that within mUM, conventional immune checkpoint regulators (CTLA-4, PD1 and PD-L1) were low and that immune suppressive genes (e.g., HLA-DRA , CD38 , CD74 , LGALS3 ) were increased [ 26 ].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Any tumour infiltrating lymphocytes (TILs) present in mUM were CD8+ T-cells with low expression of cytotoxic markers, such as Granzyme B, and they were typically “excluded” from the tumour core [ 25 ]. These results, which were supported by others and suggest CD8+ T-cell exhaustion [ 27 , 28 ], were corroborated by our earlier study using NanoString analyses of six hepatic mUM by Figueiredo et al 2020 [ 26 ]. We showed that within mUM, conventional immune checkpoint regulators (CTLA-4, PD1 and PD-L1) were low and that immune suppressive genes (e.g., HLA-DRA , CD38 , CD74 , LGALS3 ) were increased [ 26 ].…”
Section: Introductionsupporting
confidence: 85%
“…As previously described [ 25 , 27 , 28 , 43 ], the predominant lymphocyte population present within most mUM were exhausted CD8+ TILs (82.5%) showing either an “altered excluded” or “altered immunosuppressed” pattern, corresponding to a low or intermediate immunoscore, respectively. Interestingly, those mUM with a “high” TIL immunoscore had upregulation of the CD25/ILR2A , corresponding to regulatory T-cells (Tregs), and thereby creating a TME characterized by immunosuppression directed against tumour antigen-specific effector T cells, B cells, and plasma cells, ultimately leading to immune exhaustion and/or anergy [ 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 60%
“…This indicates that the presence of the distinct HGPs may depend on the type of primary tumor. Comparable to what has been described for colorectal cancer [7][8][9] and uveal melanoma 12 , we confirm the association between R-HGP and poor outcome after resection of LM. In contrast, D-HGP may thus identify breast cancer patients who can be offered (repeated) hepatic surgery to prolong survival.…”
supporting
confidence: 89%
“…Importantly, we also observed that the xenografts had defining characteristics of desmoplastic or replacement HGPs [27]. Barnhill and collaborators previously determined that the replacement pattern was correlated to shorter overall survival of UM patients [30].…”
Section: Discussionmentioning
confidence: 95%